PENGEMBANGAN INSTRUMEN PENILAIAN PEMBELAJARAN MATEMATIKA BERBASIS ISPRING SUITE - Farman Farman; Shinta Anjelina; Qadriah Triatni Putri; Nur Ainnul Mardiah; Karmila Sari (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
This study aims to develop a mathematics learning instrument based on ispring suite for class VIII. This research method uses the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The research subjects were selected as many as two classes from all students of class VIII MTs. S Nurul Iman Pomalaa. The data analysis technique used a validation questionnaire and a student response questionnaire. The research results obtained (1) material expert validation got an average value of 4.31 with very valid criteria, media experts got an average value of 4.5 with very valid criteria, (2) the results of the student response questionnaire on the ease of use of mathematics learning assessment instruments were 79 ,48 is included in the practical category to use and (3) the learning outcomes of class VIII Iman students who use the ispring suite-based assessment instrument are better than the learning outcomes of class VIII Takwa students who use conventional assessment instruments and the average class response of students to the benefits and suitability of the instrument the assessment of learning mathematics is 81.2. The ispring suite-based mathematics learning assessment instrument for number pattern material meets the criteria of being valid, practical, and effective.